2017
DOI: 10.1152/ajpendo.00216.2016
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin propeptide mutation of the hypermuscularCompactmice decreases the formation of myostatin and improves insulin sensitivity

Abstract: The TGF␤ family member myostatin (growth/differentiation factor-8) is a negative regulator of skeletal muscle growth. The hypermuscular Compact mice carry the 12-bp Mstn(Cmpt-dl1Abc) deletion in the sequence encoding the propeptide region of the precursor promyostatin, and additional modifier genes of the Compact genetic background contribute to determine the full expression of the phenotype. In this study, by using mice strains carrying mutant or wild-type myostatin alleles with the Compact genetic background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…The current finding that the C42del mutation positively affected muscle growth in quail indicates an important role of the conserved cysteine 42 residue in MSTN function. Several studies demonstrated that non-frameshift mutations in MSTN propeptide inhibited proteolytic process of pro-MSTN, resulted in an absence or decrease of mature MSTN, thereby increasing muscle mass in humans and mice [3,19]. Although our trials to detect MSTN protein with commercial antibodies had been failed, it will be interesting to investigate whether proteolytic process of MSTN protein can be affected by C42del mutation in propeptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current finding that the C42del mutation positively affected muscle growth in quail indicates an important role of the conserved cysteine 42 residue in MSTN function. Several studies demonstrated that non-frameshift mutations in MSTN propeptide inhibited proteolytic process of pro-MSTN, resulted in an absence or decrease of mature MSTN, thereby increasing muscle mass in humans and mice [3,19]. Although our trials to detect MSTN protein with commercial antibodies had been failed, it will be interesting to investigate whether proteolytic process of MSTN protein can be affected by C42del mutation in propeptide.…”
Section: Discussionmentioning
confidence: 99%
“…In case of MSTN mutation in a human, insertion of 108 base-pairs in the MSTN gene encoding the propeptide region inhibited cleavage of pro-MSTN resulted in absence of mature MSTN and increase of muscle mass [3]. Similarly, decreased formation of mature MSTN resulted from a 12 base-pair deletion in the MSTN gene encoding the propeptide region in the hypermuscular mouse [19]. In avian species, alternative splicing of MSTN produces a truncated form of MSTN protein, MSTN-B, containing only a N-terminal half of propeptide region [20].…”
Section: Introductionmentioning
confidence: 99%
“…Catabolic pathways include e.g., activation of the ubiquitin-proteasome system, caspase-3-mediated apoptosis, autophagy, imbalance between the anabolic insulin/IGF1 and catabolic myostatin signaling pathways, IL-6 and TNF-α-mediated inflammatory pathways, defective leptin signaling and hypothalamic melanocortin systems, over-activated SNS and RAAS, etc. (Mitch and Du, 2004 ; see for detailed reviews: Mendler et al, 2007 ; Wang and Mitch, 2014 ; Yoshida and Delafontaine, 2015 ; Powers et al, 2016 ; Kocsis et al, 2017 ) (Figure 2 ). These pathways might activate each other and lead to CKD-associated complications including, e.g., hypertension, insulin resistance, metabolic changes, chronic inflammatory state, malnutrition etc (Mitch and Du, 2004 ; Wang and Mitch, 2014 ; Yoshida and Delafontaine, 2015 ; Powers et al, 2016 ) (Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…TBC1D4 is associated with skeletal muscle growth, as TBC1D4 signaling is enhanced upon inactivation of the myokine myostatin (Kocsis et al 2017). Myostatin has been shown to be a negative regulator of muscle growth and development that inhibits proliferation and differentiation in myogenic cells as well as protein synthesis in existing muscle fibers (Chen & Lee 2016).…”
Section: Rabgaps Are Linked With Skeletal Muscle Development Via Ir Amentioning
confidence: 99%
“…However, neither phosphorylation state nor protein abundance of TBC1D1 were determined in mice exhibiting loss of myostatin activity. Therefore the hypermuscular effects could also be mediated by TBC1D1, and TBC1D4 is rather responsible for the improvements in glucose tolerance as AKT phosphorylation is increased as well (Kocsis et al 2017).…”
Section: Rabgaps Are Linked With Skeletal Muscle Development Via Ir Amentioning
confidence: 99%